The Impact of Visual and Cognitive Dual-Task Demands on Traffic Perception During Road Crossing of Older and Younger Pedestrians - Wiczorek, Rebecca; Protzak, Janna (Frontiers in Psychology, 2022)
With the help of the current experiment, we wanted to learn more about the impact of visually demanding vs. cognitively demanding secondary tasks on the attention allocation of older pedestrians during the phase of traffic perception within the process of road crossing. For this purpose, we used two different road crossing tasks as well as two different secondary tasks. The road crossing “stop task” was a signal detection task, where an approaching car had to be detected. The road crossing “go task” was a dynamic visual search task, where the resolution of a busy road situation had to be identified. The visual secondary task was a static visual search task and the cognitive secondary task was a 1-back (memory) task. One younger group (≤ 30 years) and one older group (≥ 65 years) of participants completed the tasks as single vs. dual-tasks in all possible combinations. Performance was measured through errors and response time; in addition, the subjective workload was assessed via NASA-TLX. Analyses show that the visual secondary task reduces performance in the road crossing more strongly than the cognitive task, while the visual task itself is less impaired by the road crossing tasks than is the cognitive task. Overall, performance diminishes from single to dual-task completion. Results further indicate age effects in terms of increased errors and response time for older compared to younger participants. In addition to these age effects, age specific dual-task effects emerge for response time in the go task along with the visual task as well as for response time in the cognitive task along with the go task. Subjective workload is higher in the dual-task conditions than in the single-tasks. Findings are discussed with regard to theoretical and practical implications.